1998
DOI: 10.1063/1.367937
|View full text |Cite
|
Sign up to set email alerts
|

Sm 2 (Co,Fe,Cu,Zr) 17 magnets for use at temperature ⩾400 °C

Abstract: Sintered Sm2(Co,Fe,Cu,Zr)17 magnets with improved high temperature performance have been obtained by reducing the iron content in the magnet alloys. A record intrinsic coercive force, HCI, of 8.3 kOe at 400 °C was obtained when the iron content was decreased to 7 wt%. At 400–600 °C, 2:17 magnets with low iron content have demonstrated lower irreversible loss of magnetic flux, higher maximum energy product, and lower temperature coefficient of HCI. A temperature coefficient of HCI=−0.12%/°C (20–400 °C) was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Similarly, magnets which have not been heat treated optimally (Ta too low, t a too short) also show smaller cell sizes and therefore less Cu in the cell walls. In contrast, in the Cu-rich case the equilibrium is completely shifted to the left leading to a entirely different temperature behaviour of the wall energies -ý"5 and -2 y: 7 and therefore to a strongly negative temperature coefficient of the coercivity according to eq. (2) and eq.(3).…”
Section: Coercivity Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, magnets which have not been heat treated optimally (Ta too low, t a too short) also show smaller cell sizes and therefore less Cu in the cell walls. In contrast, in the Cu-rich case the equilibrium is completely shifted to the left leading to a entirely different temperature behaviour of the wall energies -ý"5 and -2 y: 7 and therefore to a strongly negative temperature coefficient of the coercivity according to eq. (2) and eq.(3).…”
Section: Coercivity Mechanismmentioning
confidence: 99%
“…For a further improvement of the performance of polymer bonded magnets and the hightemperature magnetic properties, especially the temperature stability of the coercivity, the most important prerequisite for both hard magnetic materials is the detailed analysis of the hardening mechanisms and in the case of Sm 2 (Co,Cu,Fe,Zr)1 7 additionally of its formation. It is nowadays generally accepted that in RE 2 Fe1 4 B based materials the nucleation mechanism governs the coercivity, whereas in Sm 2 Co1 7 based materials domain wall pinning processes are dominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [17,18] suggested that the high temperature performance of SmCo 2:17 magnets can be improved by decreasing the Fe content. Our results show that for some compositions the addition of a certain amount of Fe is necessary to develop a uniform cellular microstructure with a larger cell size and thus a high coercivity.…”
Section: Effect Of Fementioning
confidence: 99%
“…9) In this study, the use of the glass slag method in the extraction of Sm from the Sm-Co magnets, which have become renewed interests as the high temperature permanent magnets. 10,11) The degree of the extraction of Sm from the Sm-Co alloys is evaluated by chemical and microstructural analyses of the Sm-Co alloys processed by the glass slag method.…”
Section: Introductionmentioning
confidence: 99%